1989
DOI: 10.1111/j.1432-1033.1989.tb14749.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the gene encoding the 14‐kDa subunit VII of yeast ubiquinol

Abstract: The single nuclear gene encoding the 14‐kDa subunit VII of yeast ubiquinol:cytochrome c oxidoreductase has been inactivated by one‐step gene disruption, as verified by Southern blot analysis and immunoblotting. The resulting mutant has no ubiquinol:cytochrome c oxidoreductase activity and is respiratory‐deficient. Immunoblotting shows that cells lacking the 14‐kDa protein, also have lowered steady‐state levels of other subunits of complex III, the nuclear‐encoded 11‐kDa subunit VIII, the Rieske Fe‐S protein an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…Results obtained earlier in our laboratory with a QCR7 disruption mutant in the wild-type strain HR2 showed that functional complementation was only possible after reintegration of the QCR7 gene into its original locus [20].…”
Section: Episomal Complementation Of Yeast Strain Dll-qcr7"mentioning
confidence: 96%
See 3 more Smart Citations
“…Results obtained earlier in our laboratory with a QCR7 disruption mutant in the wild-type strain HR2 showed that functional complementation was only possible after reintegration of the QCR7 gene into its original locus [20].…”
Section: Episomal Complementation Of Yeast Strain Dll-qcr7"mentioning
confidence: 96%
“…Western blot analysis on mitochondria1 protein isolated from 0.3% glucose, 2% galactose-grown cells of D11, D11-QCR7", and from null mutants transformed with either YCp-QCR7 or YEP-QCR7 showed that the Dll-QCR7" mutant has the same phenotype as described for the HR2-QCR7" mutant [20] and that, due to the absence of a complete QCR7 promoter [20], complementation of the QCR7" strain with the single copy plasmid YCp-QCR7 does not completely restore the levels of cytochrome 6, the Rieske FeS-protein and the 11-kDa subunit to the wild-type levels, while complementation with the multi-copy plasmid YEP-QCR7 does (data not shown, but see Fig. 5).…”
Section: Episomal Complementation Of Yeast Strain Dll-qcr7"mentioning
confidence: 99%
See 2 more Smart Citations
“…The petite phenotype resulting from deletion of subunit 9 differs from that which results from deletion of other nuclearencoded subunits, in that the subunit 9 deletion strain assembles an optically detectable cytochrome bc~ complex. In contrast, the loss of bc~ complex activity which results from deletion of core protein 1 [8], subunit 7 [9], or subunit 8 [10], can be attributed to lack of cytochrome b and/or incomplete assembly of the remaining subunits of the complex.…”
Section: Introductionmentioning
confidence: 99%